2017
DOI: 10.1021/acs.jmedchem.7b00058
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Receptor for Advanced Glycation Endproducts (RAGE): A Medicinal Chemistry Perspective

Abstract: The receptor for advanced glycation endproducts (RAGE) is an ubiquitous, transmembrane, immunoglobulin-like receptor that exists in multiple isoforms and binds to a diverse range of endogenous extracellular ligands and intracellular effectors. Ligand binding at the extracellular domain of RAGE initiates a complex intracellular signaling cascade, resulting in the production of reactive oxygen species (ROS), immunoinflammatory effects, cellular proliferation, or apoptosis with concomitant upregulation of RAGE it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
191
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(198 citation statements)
references
References 134 publications
(646 reference statements)
2
191
0
5
Order By: Relevance
“…Inflammation and cancer sharing many signaling pathways, the role of RAGE in carcinogenesis and the link with cell transformation, apoptosis and metastasis has been established 16,45,46 . Therefore, RAGE has become an attractive target for therapeutic purpose 7 . In this study, we found that administration of FPS-ZM1, a specific inhibitor of RAGE, resulted in improvements of gut damage during enteritis and colitis development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation and cancer sharing many signaling pathways, the role of RAGE in carcinogenesis and the link with cell transformation, apoptosis and metastasis has been established 16,45,46 . Therefore, RAGE has become an attractive target for therapeutic purpose 7 . In this study, we found that administration of FPS-ZM1, a specific inhibitor of RAGE, resulted in improvements of gut damage during enteritis and colitis development.…”
Section: Discussionmentioning
confidence: 99%
“…The receptor for advanced glycation end products (RAGE) is a cell surface multiligand receptor of the immunoglobulin superfamily. RAGE is expressed in all tissues either constitutively or upon inflammation, and is widely localized in many cell types (hepatocytes, smooth muscle cells, neurons, peritoneal mesothelial cells, immune cells or epithelial cells…) [7][8][9][10] . RAGE is considered as a pattern recognition receptor, responding to danger signals and recognizing a three-dimensional structure rather than a specific amino acid sequence 11 .…”
mentioning
confidence: 99%
“…Extracellular S100B has also been shown to interact with surrounding cell types through the Receptor for Advanced Glycation Endproducts (RAGE) (Hofmann et al 1999;Huttunen et al 2000). RAGE is a ubiquitous, transmembrane immunoglobulin-like receptor that binds to a diverse range of extracellular ligands and intracellular effectors, initiating a complex intracellular signaling cascade, which may also be associated with a series of pathological conditions, including neuroinflammatory reaction to neural injury, and concomitantly resulting in an up-regulation of RAGE itself (for review, Bongarzone et al 2017). Data have also been reported indicating that extracellular S100B is captured by vesicles and re-uptaken by astrocytes in a RAGE-dependent manner (Lasic et al 2016).…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 99%
“…5 AGEs mediate their pathological effects through activation of signaling cascades after binding to the receptor for advanced glycation end products (RAGE). 6 The insulin resistance (IR), an important pathological feature of MS, 7 occurs because of the defective insulin action both in the liver and in muscle. 8 This IR, associated with concomitant hyperinsulinemia, may potentiate other MS components such as hypertriglyceridemia and fatty liver.…”
Section: Introductionmentioning
confidence: 99%